Clarifying the Complexities of Qualitative Research: A Book Review of Phillip Adu’s A Step-by-Step Guide to Qualitative Data Coding - Lee, Gyeonghwa (Qualitative report, 2021)
Handling a large number of diverse types of qualitative data can be challenging for qualitative researchers. Also, there seems to be no clear standard for qualitative data analysis unlike the quantitative form. This is one of the main reasons for difficulties in analysing qualitative data and may cause concerns about the issue of research credibility. Dr Adu’s book may help to solve such worries and challenges by providing a step-by-step qualitative data coding process from setting up the research paradigms to presenting findings systematically, concretely, and comprehensively.